Effects of Silk Degumming Process on Physicochemical, Tensile, and Optical Properties of Regenerated Silk Fibroin. Issue 12 (21st September 2018) - Nultsch, Kira; Bast, Livia K.; Näf, Muriel; Yakhlifi, Salima El; Bruns, Nico; Germershaus, Oliver
Abstract: Sericin removal from silk (degumming) affects material characteristics of silk fibroin (SF). Sodium carbonate is most commonly used for degumming, but numerous alternative methods are available. Herein, a systematic comparison of degumming methods is provided. Sodium carbonate, sodium oleate, trypsin, and ionic liquid are used, and materials are characterized regarding mass loss, SF content, molecular integrity of SF, refractive index, and tensile properties. Complete degumming is achieved within 30 min of using sodium carbonate, but results in significant reduction of molecular weight, shift toward less acidic charge variants, and reduction of yield‐ and rupture force. Sodium oleate and trypsin are inefficient and negatively affect tensile properties, while ionic liquid shows good efficiency and marginal degradation of SF but also reduced yield‐ and rupture force. Refractive index is not affected by degumming. These results allow rational selection of the degumming method and tuning of SF properties for biomedical applications. Abstract : The degumming of virgin silk significantly influences the physicochemical properties and material characteristics of resulting silk fibroin. The efficiency of different degumming methods and their effect on mass loss, silk fibroin content, molecular weight, and charge as well as on tensile and optical properties is investigated to allow rational process selection for biomedical applications.